Comparative analysis of the collection winter barley samples in the Rostov region - E. S. Doroshenko; E. G. Filippov (Зерновое хозяйство России)
The main task for the near future is to identify the best samples from the collection to develop the winter barley varieties that meet the modern requirements of domestic agricultural producers. The purpose of the study was to identify the effect of the yield structural elements and other traits on the productivity of collection winter barley varieties and to identify the most adapted for use in the breeding process. The current paper has presented the study results of collection winter barley samples. The study was carried out in the department of barley breeding and seed production of the FSBSI Agricultural Research Center «Donskoy» (2018–2021). Based on the study results of this material, there were identified new sources for use in breeding programs to increase the values of individual traits:– low stem: ‘Perkins’ (USA), ‘Novosadski 331’ (Yugoslavia);– resistance to lodging: ‘Hobbit’ (Switzerland), ‘Merchant’ (Bulgaria), ‘Akademichesky’ (Ukraine), ‘Gust’ (Belarus), ‘18513 EN11’ (France), ‘Explorer 2’, ‘Explorer 3’, ‘Explorer 4’, ‘Explorer 6’, ‘Explorer 8’, ‘Wintwalt’, ‘Tiffani’ (Germany), ‘Perkins’ (USA), ‘Novosadski 331’ (Yugoslavia), ‘Posaune’, ‘Sombrero’, ‘Karisma’ (England), ‘Duet’ (Germany);– number of productive stems per area unit: ‘Explorer 8’, ‘Explorer 4/2’, ‘Wintwalt’ (Germany), ‘Baraka’ (France), ‘Posaune’ (England);– grain content per head: ‘Artel’ (Russia), ‘Caprice’, ‘Azurel’, ‘Rurdue’ (France), ‘HWV1427’ (Germany);– 1000-grain weight: ‘Randevu’, ‘Premier’ (Russia), ‘Nectaria’, ‘Vanessa’ (France), ‘Explorer 3’ (Germany);– grain weight per head: ‘Randevu’, ‘Pallidum 1916’ (Russia), ‘Oribi’, ‘Bezosty’ (France), ‘Explorer 2’, ‘KWS-Scala’ (Germany), ‘Hobbit’ (Switzerland);– fast-maturity: ‘Parallelum 1963’, ‘Sekret,’ ‘Bezosty 1953’, ‘Bezosty 1954’ (Russia), ‘Fermer’ (Ukraine);– high productivity: ‘Rostovsky 55’, ‘Grand’, ‘Artel’ (Russia), ‘KWS-Hiskory’, ‘Explorer 8’ (Germany), ‘Esterel’ (France).According to the complex of economically valuable traits (4 or more traits), there were identified 15 varieties: ‘Randevu’, ‘Parallelum 1960’ (Russia), ‘KWS-Scala’, ‘KWS-2-117’, ‘KWS-2-234’, ‘Explorer 4’, ‘Explorer 3/2’ (Germany), ‘Baraka’, ‘Rebelle’, ‘6577 CH’, ‘18513 EH11’ (France), ‘Cello’, ‘Fenesse’ (USA), ‘Novosadski 321’ (Yugoslavia), ‘Posaune’ (England).